Entecavir: A Review and Considerations for Its Application in Oncology - Tânia Lourenço; Nuno Vale (MDPI AG, 2023)
Entecavir (ETV) is a drug used as a first-line treatment for chronic hepatitis B (CHB) virus infection because it is a guanosine nucleoside analogue with activity against the hepatitis B virus polymerase. The ETV dosage can range from 0.5 mg to 1 mg once a day and the most common side effects include headache, insomnia, fatigue, dizziness, somnolence, vomiting, diarrhea, nausea, dyspepsia, and increased liver enzyme levels. In addition to its conventional use, ETV acts as an inhibitor of lysine-specific demethylase 5B (KDM5B), an enzyme that is overexpressed in breast, lung, skin, liver, and prostate tumors and is involved in the hormonal response, stem cell regeneration, genomic stability, cell proliferation, and differentiation. The KDM5B enzyme acts as a transcriptional repressor in tumor suppressor genes, silencing them, and its overexpression leads to drug resistance in certain tumor types. Furthermore, the literature suggests that KDM5B activates the PI3K/AKT signaling pathway, while reducing KDM5B expression decreases AKT signaling, resulting in decreased tumor cell proliferation. In silico studies have demonstrated that ETV can inhibit tumor cell proliferation and induce apoptosis by reducing KDM5B expression. ETV also appears to inhibit PARP-1, has a high genetic barrier, reducing the chance of resistance development, and can also prevent the reactivation of the hepatitis B virus in cancer patients, which have proven to be significant advantages regarding its use as a repurposed drug in oncology. Therefore, ETV holds promise beyond its original therapeutic indication.